Evaluation of the effect of different points of orthodontic force application (A typodont study) - Omar KhM Thiab; Ahmed A Abdul- Mawjood; Ahmed Gh Mohammed (University of Mosul, College of Dentistry, 2011)
Aims: To determine the effect of different points of force application on dimensional positions and the ratio of space closure of maxillary canine using sliding mechanics. Materials and Methods: The study included eight groups which were categorized according to the differences in the points from which the retraction force was applied. A 180 gm was applied by short elastic chain to retract the right maxillary canine on 0.0180.025'' rectangular stainless steel (SS) wire and along 13 mm available space. In both vertical and horizontal direction, photographs were taken by digital camera and the angle between canine extension bar and bite plane extension bar was measured by protractor to determine tipping and rotation whereas rate of space closure was measured by digital vernia. Results: The results showed that the maximum rate of space closure was achieved when elastic chain was attached between molar hook to canine hook and the minimum degree of tipping was achieved when elastic chain attached between premolar bracket to canine hook while minimum rotation occurred when the attachment was between premolar hook to canine hook. Conclusions: Changing the distance between the points of force application significantly affects the rate of space closure, tipping and rotation. The use of hook significantly increases the rate of space closure and decreases tipping and rotation.